Antidepressants and unresponsive episodes in the elderly. (17th July 2012) - McGuinness, James; Delicata, Mark
Abstract : We present a case where initiation of antidepressant therapy was associated with an episode of unresponsiveness. Providing the opportunity to examine the possible pitfalls in geriatric prescribing.